Exploration of Solutions for Unmanned Smart Farmland - Wang, Zhao; Sun, Xunbo (International Journal of Natural Resources and Environmental Studies, 2024)
Unmanned smart farmland is an advanced stage of agricultural production, which integrates emerging technologies such as the Internet of Things, cloud computing, big data, 5G, artificial intelligence equipment and robots. It relies on the smart agricultural production system deployed on the agricultural production site to achieve full automatic control of facilities, equipment, machinery, etc. or autonomous control of robots, realizing intelligent perception, intelligent warning, intelligent decision-making, intelligent analysis, and expert online guidance of the agricultural production environment. It is a 24/7, full process, and full space unmanned production operation mode, essentially realizing machine replacement in agricultural production. Building unmanned smart farmland is an important way to alleviate the shortage of rural labor and promote the modernization of agriculture and rural areas. It provides precise planting, visual management, and intelligent decision-making for agricultural production, and also allows agriculture and rural areas to share the achievements of technological development in the times.